Keanekaragaman Kultivar Pisang (Musa spp.) Berdasarkan Karakter Biokimia Pada Berbagai Ketinggian Tempat di Kabupaten Boyolali - Adimas, Lastya; Suratman; Solichatun (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the effect of differences in growing places altitude on the diversity of biochemical characters (glucose, vitamin C, and folic acid) of three banana cultivars (Musa acuminata (AAA)/ambon, Musa balbisiana (BBB)/kepok, and Musa paradisiaca (AAB)/raja) grown in Boyolali Regency. The study was conducted at three growing places altitudes: Kemusu (123 masl), Musuk (667 masl), and Gladagsari (806 masl). Biochemical content data were tested quantitatively using UV-Vis spectrophotometry and a refractometer, with five replications per location, then analyzed using ANOVA. The results showed significant variation between cultivars and locations in terms of vitamin C and folic acid levels, with the Musa balbisiana (BBB)/kepok cultivar in Musuk having the highest vitamin C content. Furthermore, environmental factors such as light intensity and temperature significantly influenced the variation in biochemical content. This study strengthens the understanding of the interaction between genotype and environmental factors (G × E interaction) in shaping the nutritional quality of bananas. In conclusion, the selection of appropriate cultivars and planting locations can optimize the nutritional value of bananas.